Identifikasi Distribusi Beban Sedimentasi pada Intake DAM dan Reservoir PLTA (Studi Kasus: PLTA Cirata, Purwakarta – Jawa Barat) - Asep Irwan; Ari Wicaksono; Firda Aulia Khairin (Institut Teknologi Sains Bandung, 2020)
Reservoirs in Indonesia are almost inseparable from the problem of sedimentation. Sedimentation issues are important in reservoir operations, including those that affect reservoir life. One of them is in the PLTA Cirata which experienced a high amount of sedimentation, based on the results of research by BPWC in 2017 the value of sedimentation was 1.96 million m3/year. The results obtained 1,565,844.51 m3 / year so that when compared with this value has a difference between 394,155.49 m3 / year, this occurs because of differences in the sedimentation calculation method. The research method uses the MIKE 21 Module (Flow Model), this research can provide information related to the sedimentation load in the PLTA Cirata. Sediment load that occurs in the intake area of the modeling results is from the Cikundul watershed with a maximum flow value in one year in 2018 of 716.14 m3/s occurred in April. As for the thickness of sediment occurs first 1-month simulation results in the location of each estuary is between 0.01 to 0.15 m for the location of the dam area of 0.01 to 0.03 m. The thickness of sediments in the Cirata area at the location of the river mouth is around ± 1.8 m / year and at the dam around ± 0:36 m / year. Types of sediment in each river mouth obtained 21.21% sand, 78.48% silt, and 0.31% gravel, for the dam area obtained 24.49% sand, 75.08% silt, and 0.43% gravel. It can be concluded that sedimentation entering the Intake area is removing sediment from each watershed namely Cikundul, Cibalagung, Cisokan, Citarum, and Cicendo.